The Implementation of Text-Based Approach within the School Based Curriculum in Junior High School - Irawansyah, Egi; Regar, Lila Aprina; Farhansyah, Muhammad; Hasibuan, Kalayo (Lembaga Riset dan Inovasi Almatani, 2024)
The text-based approach has garnered significant attention for its potential to enhance literacy and critical thinking skills. This methodology emphasizes the use of texts as of education, innovative teaching methodologies are crucial for cultivating comprehensive learning central tools for learning across various subjects, aligning with pedagogical goals of fostering deeper comprehension, analytical abilities, and effective communication. Implementing a text-based approach within a junior high school curriculum presents a unique opportunity to engage students meaningfully, preparing them for the complex literacy demands of the modern world. This paper explores the rationale, implementation strategies, and potential outcomes of incorporating a text-based approach in junior high school education. Supported by expert opinions and research findings, the study highlights the efficacy of this approach in promoting higher-order thinking skills and academic success. By focusing on texts, students can develop a nuanced understanding of subjects, enhance their analytical skills, and improve their communication abilities, which are essential for their future academic and professional endeavors.